STRATEGI KOMUNIKASI PEMASARAN PETERNAK LOVEBIRD DALAM MENINGKATKAN LOYALITAS PELANGGAN - Herru Prasetya Widodo; Ellen Meianzi Yazak (REFORMASI, 2018)
n business activities, market segmentation, targeting and positioning are used to select target markets, look for opportunities, undermine segments leaders, formulate communication messages, serve better, analyze consumer behavior, design products, and more. Besides as an archipelagic country, our country is an agrarian country whose society is mostly farmed or raised. Through planning a good marketing communication strategy then it is expected that the community can implement marketing well. For example, in terms of livestock, an innovation can help realize the initial target in improving the livelihood of farmers. Breeding lovebird birds into one of the most promising business, considering the many enthusiasts of this bird in the market. In addition, lovebird has also become one of the most popular birds in the country. Bird lovebird lately became a bird whose demand continues to grow, because not only in big cities are interested to keep this bird, in the countryside began many bermiant to have it, even to the interest to develop a breedeer (breeder) usually have their own way in breeding this very interesting bird. Indeed, lovebird comes from the African continent. This bird is monogamous, but can also be cultivated by polygamy. Bird lovebird has a voice that is very character, famous for its peculiar sounds. The purpose of this study is to find out the marketing communication strategy of lovebird breeders in improving customer loyalty to improve their income living standards and expand market share. This research was conducted on some Lovebird breeders in Malang City. The method used is descriptive qualitative with data collection technique through interview and documentation by using purposive sampling. The data analysis using interactive analysis. That includes data reduction, data presentation, and verification or interpretation of data. The result of research has been done that marketing communication strategy conducted by some farmers in selling lovebird birds using social media like facebook and community network and branding their lovebird birds using ring with the name of breeder and mobile phone number that can be contacted to increase customer loyalty .